Ferhoun ka mujisema - Jahangir Maqbool (Ferozesons; Lahore, 2010)
"Ferhoun Ka Mujassama" is a compelling narrative that delves into themes of power, tyranny, and the lessons of history through the symbol of Pharaoh's statue.